Overview of Experimental and Clinical Findings regarding the Neuroprotective Effects of Cerebral Ischemic Postconditioning. (4th April 2017) - Ma, Di; Feng, Liangshu; Deng, Fang; Feng, Jia-Chun
Abstract : Research on attenuating the structural and functional deficits observed following ischemia-reperfusion has become increasingly focused on the therapeutic potential of ischemic postconditioning. In recent years, various methods and animal models of ischemic postconditioning have been utilized. The results of these numerous studies have indicated that the mechanisms underlying the neuroprotective effects of ischemic postconditioning may involve reductions in the generation of free radicals and inhibition of calcium overload, as well as the release of endogenous active substances, alterations in membrane channel function, and activation of protein kinases. Here we review the novel discovery, mechanism, key factors, and clinical application of ischemic postconditioning and discuss its implications for future research and problem of clinical practice.